Recent advances in the molecular targeted drugs for prostate cancer - Gao, Pudong; Li, Tao; Zhang, Kuiyuan; Luo, Guangheng (International urology and nephrology, 2023)
Context Prostate cancer (PCa) is the second largest male tumor in the world and one of the most common malignant tumors in the urinary system. In recent years, the incidence rate of PCa in China has been increasing year by year. Meanwhile, refractory hormone resistance and adverse drug reactions of advanced PCa cause serious harm to patients. Objective The present study aims to systematically review the recent advances in molecularly targeted drugs for prostate cancer and to use the retrieval and analysis of the literature library to summarize the adverse effects of different drugs so as to maximize the treatment benefits of targeted therapies. Evidence acquisition We performed a systematic literature search of the Medline, EMBASE, PubMed, and Cochrane databases up to March 2022 in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. Medical Subject Heading (MeSH) terms and keywords such as (prostate cancer) AND (molecular target drugs) AND (side effect) were used. No language restrictions were set on the search process, and all these results were processed independently by two authors. Consensus was reached through discussion once met with any disagreements. The primary endpoint was differential features between different molecular targeted drugs. Secondary endpoints were side effects of different drugs on the body and corresponding prognostic values. Evidence synthesis The Cochrane Collaboration risk of bias tool was used to assess the study quality in terms of sequence generation, allocation concealment, blinding, the completeness of outcome data, selective reporting and other biases. We retrieved 332 articles, of which 49 met the criteria for inclusion. Included studies show that prostatic tumor cells, tumor neovascularization and immune checkpoints are the main means for targeted therapy. Common drugs include 177 Lu-PSMA, Olaparib, Rucaparib, Bevacizumab, Pazopanib, Sorafenib, Cabozantinib, Aflibercept, Ipilimumab, Atezolizumab, Avelumab, Durvalumab. A series of publicly available data suitable for further analysis of side effects. An over-representation analysis of these datasets revealed reasonable dosage and usage is the key to controlling the side effects of targeted drugs. Important information such as the publication year, the first author, location and outcome observation of adverse effects was extracted from the original article. If the study data has some insufficient data, contacting the corresponding authors is necessary. All the studies included prospective nonrandomized and randomized research. Retrospective reviews were also screened according to the relevant to the purpose of this study. Meeting abstracts as well as letters to the editor and editorials were excluded. Statistical analysis Data analysis was based on Cochrane's risk of bias tools to obtain the quality assessment. The included randomized studies used RoB2 and non-randomized ones corresponded to ROBINS-I. Standardized mean differences (SMD) were used to determine relative risk (RR) and side effects between groups. The eggers’ test was used to check the publication bias from variable information in the included studies. All p < 0.05 were considered to be significant, and 95% was set as the confidence interval. Conclusions With the approval of a variety of targeted drugs, targeted therapy will be widely used in the treatment of advanced or metastatic prostate cancer. Despite the existence of adverse reactions related to targeted drug treatment, it is still meaningful to adjust the drug dosage or treatment cycle to reduce the occurrence of adverse reactions, improving the treatment benefits of patients.